Americanizing the Teachers: Identity, Citizenship, and the Teaching Corps in Hawai'i, 1900–1941. Issue 2 (May 2014) - Morgan, Michelle
Abstract: During the territorial period, elites and administrators in Hawai'i sought to Americanize their multiracial teaching force. This article argues that administrators applied cultural, legal, and linguistic filters to weigh teachers' potential to Americanize their students. Teachers' responses challenged elite notions of American identity and the role of education in a democracy.